Analysis of Accounting Data Mutation at Company Closing Times Listed in IDX of 2018 - Dheny Biantara; Sri Handayani (Journal of International Conference Proceedings (JICP), 2019)
Listed companies on the Indonesia Stock Exchange (IDX) are required to submit financial statement reporting annually to the IDX in accordance with the stipulated provisions. Companies made cut off period to close the book (closing), but there will be a lot of mutations of the accounts contained in the accounting financial statement of the company concerned. With the help of accounting systems (software) that exist today, the mutation of data can be detected based on the amount of data to see how these mutations was occur in several companies that are already listed on the IDX. Accounting system software helps us to expect that the transfer of data at the end of the financial statements is not significant. This research was conducted to see the magnitude of mutations that occur in companies that use the SAP system. The results of this study illustrate that the mutations made by the company at the end period of 2018 show some data mutations that can be explained as quantities that should be eliminated as small as possible if the transaction data input process is carried out properly controlled and free from some interests that usually accompany the accounting closing process a company